Farm-level productivity of Millet, Groundnut, and Cowpea under climate- smart practices using participatory - Akinseye, Mathew Folorunso; Faye, Aliou; Diouf, Doudou; Zagre, Inoussa; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The fact sheet outlines the implementation of AICCRA intervention in 2023 across three clusters (Daga Birame, Thiel, and Meouane) to promote climate-smart agriculture and innovation, utilizing participatory research and extension practices. The interventions, focusing on millet, groundnut, and cowpea, demonstrated increased yields and improved seed quality. Results indicate substantial improvements in peanut yield production, with increases from 680kg to 2222kg when comparing local to improved varieties. The introduction of climate-smart technologies, such as micro-dosing fertilizer application and improved crop varieties, significantly impacted groundnut, cowpea, and millet production across the clusters. The study emphasizes the potential of AICCRA's climate-smart technologies to enhance farm-level productivity based on climate-based agro advisory dissemination.